TECHNOLOGY, INNOVATION, AND DEVELOPMENT IN EXPORT ORIENTED DEVELOPING ECONOMIES: A COMPARISON OF THE KOREAN AND TURKISH ECONOMIES - Özgür Sarı (Sosyal Ekonomik Araştırmalar Dergisi)
The study aims to analyze the role of technological improvements and innovations in the economic development of newly emerging and developing countries and export oriented economies. Declining of the mass production systems and rising of technology and design oriented production in the globalized world economy force developing countries to integrate their export oriented economies to the global system through technological improvements and innovations. The Turkish and South Korean economies were compared in the study around the arguments about technology, innovation, and development through some sociological theories related to development. Although Turkey has started economic liberalization and development before Korea, Korea has achieved higher development level than Turkey. The parameters behind to Korean experience and the comparison to the Turkish development process will be evaluated